P07.06 A low cost, hand-held point of care molecular diagnostic device for sexually transmitted infections. (13th September 2015) - Mackay, RE; Branavan, M; Craw, P; Naveenathayalan, A; Sadiq, ST; Balachandran, W
Abstract : Introduction: Rapid and accurate field diagnostics have potential to impact on the burden of STIs in resource poor settings. Microfluidic and nano technologies offer opportunities to create molecular detection platforms but costs may be prohibitive. We present a low cost isothermal amplification, point of care test for rapid identification of sexually transmitted infections. Sample collection integrates directly with a microfluidic device for automated sample preparation, isothermal amplification and optical detection. Methods: Cell lysis, within the microfluidic cartridge, is conducted using a chemical method and nucleic acid purification is achieved on activated cellulose membrane. The microfluidic device incorporates passive mixing of lysis-binding buffers and sample using a serpentine channel. Isothermal amplification is conducted using thermophillic helicase dependent amplification (tHDA) and recombinase polymerase amplification (RPA). A low cost real-time isothermal amplification platform has been developed capable of running six amplifications simultaneously. Results: Results have shown extraction efficiencies for the new membrane of 69% and 57% compared to commercial Qiagen extraction of 85% and 59.4% for 0.1 ng/µL and 100 ng/µL salmon sperm DNA respectively spiked in phosphate buffered solution. Extraction experiments using the serpentine passive mixer cartridges incorporating lysis and nucleic acid purification showed extraction efficiency around 80% of the commercial Qiagen kit. The platform is capable of detecting 1.32 × 10 6 copies of target DNA through thermophillic helicase dependent amplification and 1 × 10 5 copies of Chlamydia trachomatis genomic DNA within 10 min through RPA. Conclusion: We have produced a low cost, rapid nucleic acid extraction, isothermal amplification and detection platform consistent with use remote resource poor settings. The simple optics setup demonstrated high sensitivity and rapid detection of the tHDA and RPA reactions removing the requirement for expensive dichroic filters and lenses. Diagnostic performance of the device is currently being undertaken. Disclosure of interest statement: No Disclosure of interest.